COMPUTER ASSISTED LANGUAGE LEARNING - O. I. Maximova (Финансы: теория и практика)
The article presents a general overview of the teaching and learning of foreign languages through multimedia and computer technology. Since its introduction, this practice has undergone significant changes in the content, approaches and methods of implementation on its development path. It has gone through several stages, which were determined by the level of computerization, the development of technologies in the field of communication and the emergence of new software products. This provision, in turn, has enabled the development of a significant number of types and kynds of tasks. The variety of these exercises and their functional capabilities is increasing along with the development of computer technology. At the present stage, practitioners working in the field of teaching foreign languages with the help of multimedia and computer technologies, are facing a number of tasks. They were developed as a result of a study commissioned by the educational unit of the European Union and formulated in a number of documents published in the early 2000s. As a result, task forces were established to develop recommendations and training programs at different regional levels and stages of teaching. The creation of relevant Internet sites has enabled specialists to become aware of the ongoing innovation processes. This experience should be studied and adopted by domestic specialists. The article presents a general overview of the teaching and learning of foreign languages through multimedia and computer technology. Since its introduction, this practice has undergone significant changes in the content, approaches and methods of implementation on its development path. It has gone through several stages, which were determined by the level of computerization, the development of technologies in the field of communication and the emergence of new software products. This provision, in turn, has enabled the development of a significant number of types and kynds of tasks. The variety of these exercises and their functional capabilities is increasing along with the development of computer technology. At the present stage, practitioners working in the field of teaching foreign languages with the help of multimedia and computer technologies, are facing a number of tasks. They were developed as a result of a study commissioned by the educational unit of the European Union and formulated in a number of documents published in the early 2000s. As a result, task forces were established to develop recommendations and training programs at different regional levels and stages of teaching. The creation of relevant Internet sites has enabled specialists to become aware of the ongoing innovation processes. This experience should be studied and adopted by domestic specialists.